Apigenin Alleviates Intervertebral Disc Degeneration via Restoring Autophagy Flux in Nucleus Pulposus Cells - Xie, Chenglong; Shi, Yifeng; Chen, Zuoxi; Zhou, Xin; Luo, Peng; Hong, Chenxuan; Tian, Naifeng; Wu, Yaosen; Zhou, Yifei; Lin, Yan; Dou, Haicheng; Wu, Aimin; et al. (Frontiers in Cell and Developmental Biology, 2022)
Oxidative stress-induced apoptosis and senescence of nucleus pulposus (NP) cells play a crucial role in the progression of intervertebral disc degeneration (IVDD). Accumulation of studies have shown that activated autophagy and enhanced autophagic flux can alleviate IVDD. In this study, we explored the effects of Apigenin on IVDD in vitro and in vivo. Apigenin was found to inhibit tert-butyl hydroperoxide (TBHP) induced apoptosis, senescence and ECM degradation in NP cells. In addition, Apigenin treatment can restore the autophagic flux blockage caused by TBHP. Mechanistically, we found that TBHP may induce autophagosome and lysosome fusion interruption and lysosomal dysfunction, while Apigenin alleviate these phenomenon by promoting the nuclear translocation of TFEB via AMPK/mTOR signaling pathway. Furthermore, Apigenin also exerted a protective effect against the progression of IVDD in the puncture-induced rat model. Taken together, these findings indicate that Apigenin protects NP cells against TBHP-induced apoptosis, senescence and ECM degradation via restoration of autophagic flux in vitro, and it also ameliorates IVDD progression in rats in vivo, demonstrating its potential for serving as an effective therapeutic agent for IVDD.